Graphene aerogel, regenerated catalyst, application of regenerated catalyst and regeneration method of CO2-rich amine solution

By using a regeneration catalyst loaded with the Lewis acidic metal component of graphene aerogel, the problems of high desorption temperature and high energy consumption of CO2-rich amine solutions are solved, and more efficient CO2 desorption and lower energy consumption are achieved.

CN119490179AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202311049627.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

The desorption temperature of CO2-rich amine solution in the existing chemical absorption method is high, resulting in high energy consumption and limiting large-scale applications.

Method used

Graphene aerogel is used as the carrier for the regeneration catalyst to support human components with Lewis acid properties, and promotes CO2 desorption reaction through the protonic acid and basic groups of graphene aerogel, reducing desorption temperature and energy consumption.

Benefits of technology

It effectively reduces the initial and end temperatures of CO2 desorption, improves the desorption rate and quantity, shortens the desorption time, reduces energy consumption, and improves the mechanical strength and recycling life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490179A_ABST
    Figure CN119490179A_ABST
Patent Text Reader

Abstract

The invention relates to the field of desorption and regeneration of a CO2-rich amine solution, and discloses a graphene aerogel, a regenerated catalyst, application of the regenerated catalyst and a regeneration method of the CO2-rich amine solution, the B acid content of the graphene aerogel is 0.001-0.05 mmol / g, the specific surface area is 40-200m < 2 > / g, and the volume of pores with the pore diameter being less than 20nm accounts for not less than 50% of the total pore volume of the graphene aerogel. The graphene aerogel is applied to a regenerated catalyst of a CO2-rich amine solution, and is beneficial to catalyzing CO2 desorption, reducing the initial temperature and the end temperature of desorption, increasing the desorption rate, shortening the desorption time, reducing the desorption energy consumption and increasing the desorption amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to CO-rich 2 The field of desorption and regeneration of amine solutions, specifically relating to a graphene aerogel, a regeneration catalyst and its application and a CO-rich 2 Method for regenerating amine solution. Background Art

[0002] CO 2 Emission reduction has become a key development strategy for China and even the world. The International Energy Agency (IEA) pointed out that CCUS (CO 2 Capture, utilization and storage (CUS) technology is the only way to achieve emission reduction targets that can directly reduce carbon emissions in key areas and reduce existing CO 2 The technology of balancing the carbon emissions that cannot be avoided. Large-scale, low-cost and commercialization will be the future development trend of CCUS projects.

[0003] Coal is currently the main type of energy in China, and coal-fired power plants are China's CO 2 The main emission source is the flue gas CO 2 Capturing, recycling, utilizing and storing carbon dioxide is the key to reducing carbon emissions in China and is also the only way for large-scale application of CCUS technology. 2 Capture technology is the most critical link in the large-scale application of CCUS technology, which determines the purity and cost of the gas source. The process energy consumption accounts for more than 60% of the total energy consumption of CCUS projects. Therefore, the reduction of energy consumption has a great impact on the CO2 reduction of flue gas. 2 Capture is crucial.

[0004] Currently used for CO 2 The capture and purification methods mainly include chemical absorption, physical absorption and physical-chemical absorption, solid adsorption, membrane treatment and cryogenic separation. However, in terms of application time, technical maturity and prospects, chemical absorption is undoubtedly the best choice at present. Chemical absorption is to selectively absorb the CO in the mixed flue gas with the absorbent. 2 Chemical reaction occurs to achieve CO 2 Separated from other gases, and regenerated by the reverse reaction of this reaction to release high-purity CO 2 For enrichment.

[0005] The main bottleneck limiting the large-scale application of chemical absorption is its high energy consumption and high cost. In order to reduce energy consumption, researchers have made efforts in two aspects: the development of efficient absorbents and the process optimization of the capture system. 2 A mesoporous solid acid-base catalyst for desorption of amine solution, wherein the mesoporous solid acid-base catalyst is Fe 2 O 3The catalyst is loaded on the carrier molecular sieve MCM-41. It is easy to separate, has good stability and can be recycled, but the temperature required for its desorption is 98°C, which is relatively high. CN106984333A discloses a loaded catalyst for regeneration of an amine solution rich in carbon dioxide. The catalyst is a metal oxide loaded sulfate-type solid superacid catalyst, wherein the carrier is γ-Al 2 O 3 , relative to SO 4 2- / ZrO 2 Catalyst and γ-Al 2 O 3 The catalyst can reduce the desorption energy consumption of ethanolamine (MEA), but the required desorption temperature is also high.

[0006] Therefore, how to further reduce the CO 2 The desorption temperature of amine solution can reduce energy consumption and is the key to reduce the chemical absorption method for capturing and purifying CO. 2 Important issues that need to be resolved urgently. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of high carbon dioxide desorption temperature and high energy consumption in the prior art, and to provide a graphene aerogel, a regeneration catalyst and its application and a CO-rich 2 A method for regenerating an amine solution. The graphene aerogel is applied to a regenerated catalyst, which can promote a desorption reaction, reduce an initial reaction temperature, and reduce energy consumption.

[0008] In order to achieve the above object, the present invention provides a graphene aerogel in the first aspect, wherein the graphene aerogel has a B acid content of 0.001-0.05 mmol / g and a specific surface area of ​​40-200 m 2 / g, the volume of pores with a pore diameter below 20nm accounts for no less than 50% of the total pore volume of the graphene aerogel.

[0009] The second aspect of the present invention provides a regenerated catalyst, which includes a carrier and a metal component loaded on the carrier; the metal component has Lewis acid properties, and the carrier is the graphene aerogel described in the first aspect.

[0010] The third aspect of the present invention provides the regenerated catalyst according to the second aspect in a CO-rich 2 Application in the regeneration of amine solutions.

[0011] A fourth aspect of the present invention provides a CO-rich 2 A method for regenerating an amine solution, under regeneration conditions, 2 The amine solution is contacted with the catalyst to produce CO 2 Desorption;

[0012] Wherein, the catalyst is the regenerated catalyst described in the second aspect.

[0013] The graphene aerogel provided by the present invention has an appropriate amount of proton acid (B acid), a suitable number of pores and a pore structure, so that it can be applied to CO-rich 2 In the regeneration catalyst of amine solution, it works synergistically with the metal component to provide not only the proton acid necessary for the desorption process, but also the necessary basic groups to promote the desorption reaction, which is beneficial to the catalysis of CO 2 Desorption, lowering the initial and end temperatures of desorption, increasing the desorption rate, shortening the desorption time, reducing the desorption energy consumption and increasing the desorption amount, and having a high mechanical strength, thereby increasing the cycle life. Preferably, it has a three-dimensional porous network structure formed by stacking two-dimensional sheet graphene, and through holes of varying sizes are distributed between the sheets, which not only ensures the shuttling of the solution, but also helps to improve the compression strength of the graphene aerogel, and further improves the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a SEM image of graphene aerogel A1 prepared in Preparation Example 1;

[0015] Figure 2 is a TEM image of graphene aerogel A1 prepared in Preparation Example 1;

[0016] Figure 3 is the X-ray photoelectron spectrum of the graphene aerogel A1 prepared in Preparation Example 1;

[0017] Figure 4 is the XPS peak spectrum of O1s of the graphene aerogel A1 prepared in Preparation Example 1;

[0018] Figure 5 is the pore size distribution curve of graphene aerogel A1 prepared in Preparation Example 1. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a graphene aerogel, wherein the graphene aerogel has a B acid content of 0.001-0.05 mmol / g and a specific surface area of ​​40-200 m 2 / g, the volume of pores with a pore diameter below 20nm accounts for no less than 50% of the total pore volume of the graphene aerogel.

[0021] According to the present invention, the graphene aerogel has an appropriate amount of proton acid (B acid), which is beneficial to improve CO 2 Preferably, the Br content of the graphene aerogel is 0.01-0.03 mmol / g. The Br content in the graphene aerogel is controlled within the above preferred range, which, together with the appropriate number of pores and pore structure, helps to promote CO 2 The desorption reaction can fundamentally reduce the reaction energy consumption.

[0022] In the present invention, the content of B acid (or L acid) is characterized by pyridine infrared method. The specific test method is as follows: 0.0089g of the sample to be tested is pressed into a self-supporting sheet with a diameter of 1.3cm, placed in an in-situ cell, the sample is evacuated at 300°C, cooled to room temperature to measure the background infrared spectrum, pyridine saturated vapor is adsorbed until the sample is saturated with adsorption, and the spectrum is recorded. After He purging for 1h, vacuum is evacuated and programmed temperature desorption (0-350°C), and the spectrum is recorded every 20°C. The standard positions of B acid and L acid in the obtained pyridine infrared spectrum are 1540cm -1 and 1450cm -1 , integrate the peaks at the corresponding positions in the figure, normalize the peak areas of the spectrum, and then calculate the acid amount according to the following formula.

[0023]

[0024] Wherein, C is the acid content, unit, mmol / g; K L / B is the absorption coefficient of L acid or B acid, which are 1.42 and 1.88 respectively, that is, K L is the absorption coefficient of L acid, which is 1.42, K B is the absorption coefficient of B acid, which is 1.88, and the unit is mmol / cm; I L / B is the peak area of ​​L acid or B acid, in cm -1 ; R is the tablet diameter, in cm; W is the tablet weight, in g.

[0025] The graphene aerogel of the present invention has a suitable number of pores and pore structure, and the specific surface area of ​​the graphene aerogel is 50-200m 2 / g, preferably 100-120m 2 / g. In the above preferred case, it can ensure that graphene aerogel is used for CO2-rich 2 When the amine solution is used to regenerate the catalyst, it is mixed with CO 2 The amine solution has a suitable contact area, which is conducive to the catalytic conversion of CO 2Desorption is beneficial to improving the mechanical strength of graphene aerogel.

[0026] In some preferred embodiments of the present invention, the total pore volume of the graphene aerogel is 0.01-0.5 mL / g, preferably 0.1-0.3 mL / g.

[0027] In some preferred embodiments of the present invention, in the graphene aerogel, the volume of pores with a pore size of less than 20 nm accounts for no less than 50% of the total pore volume of the graphene aerogel, preferably 55-90%, and more preferably 70-80%. The graphene aerogel provided by the present invention can improve the catalytic efficiency when used as a catalyst carrier by ensuring that the pores with a pore size of less than 20 nm are within a certain content range, thereby reducing the desorption temperature and shortening the desorption time, and improving the mechanical strength of the catalyst. The reason may be that the pores with a pore size of less than 20 nm are filled with metal components in the pores when the metal components are subsequently loaded to prepare the catalyst, so that the metal components are anchored on the graphene aerogel, which is conducive to exerting the activity of the metal components, and can improve the catalytic efficiency when combined with an appropriate amount of B acid, thereby reducing the desorption temperature and shortening the desorption time, and helping to reduce the loss rate of the catalyst during the regeneration process of the alcohol amine solution, and extending the service life of the catalyst.

[0028] In the present invention, the specific surface area, pore volume and pore distribution are expressed by N 2 Measured by adsorption-desorption isotherm method.

[0029] In some preferred embodiments of the present invention, X-ray photoelectron spectroscopy (XPS) is used to characterize the chemical composition of the graphene aerogel. The X-ray photoelectron spectroscopy analysis is tested on an ESCALAB250XI X-ray photoelectron spectrometer produced by Thermo Fisher Scientific, USA. The test conditions include: the excitation source is Al Kα rays, and the scanning range is 0-1200eV.

[0030] According to some preferred embodiments of the present invention, the graphene aerogel contains C, N and O elements. In the X-ray photoelectron spectrum of the graphene aerogel of the present invention, there are corresponding characteristic peaks of C, N and O, indicating that the graphene aerogel of the present invention contains C, N and O elements. The total amount of C element in the graphene aerogel is determined by the area of ​​the C1s peak in the X-ray photoelectron spectrum, the total amount of O element is determined by the area of ​​the O1s peak, and the total amount of N element is determined by the area of ​​the N1s peak. Preferably, the molar ratio of the C element, O element and N element is (1-60): (5-30): (0.5-5); preferably (15-35): (10-20): (1-2), for example, it can be 15:10:1, 15:15:1, 15:20:1, 20:10:1, 25:15:1, 25:20:1, 30:10:1, 30:15:1 Typical but non-limiting molar ratios include: 1, 30:20:1, 35:10:1, 35:15:1, 35:20:1, 15:10:2, 15:15:2, 15:20:2, 20:10:2, 25:15:2, 25:20:2, 30:10:2, 30:15:2, 35:10:2, 35:15:2, and 35:20:2.

[0031] In some preferred embodiments of the present invention, the spectrum of O1s in the X-ray photoelectron spectrum of the graphene aerogel of the present invention is composed of peaks of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen, proving that the oxygen species in the graphene aerogel include hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen is determined by the peak area of ​​the peak separation to be (1-20): (0.1-5): (1-5), preferably (1-5): (0.5-2): (1-2). For example, the molar ratios may be typical but not limiting, such as 1:0.5:1, 1:1:1, 1:1.5:1, 1:2:1, 2:0.5:1, 2:1:1, 2:1.5:1, 2:2:1, 3:0.5:1, 3:1:1, 3:1.5:1, 3:2:1, 4:0.5:1, 4:1:1, 4:1.5:1, 4:2:1, 5:0.5:1, 5:1:1, 5:1.5:1, 5:2:1, etc. Under the above preferred distribution of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen, it is beneficial to further improve the hydrophilicity of graphene aerogel and facilitate desorption.

[0032] In some preferred embodiments of the present invention, the graphene aerogel is a three-dimensional porous network structure formed by stacking two-dimensional graphene sheets.

[0033] In some preferred embodiments of the present invention, the average sheet thickness of the two-dimensional graphene flakes in the graphene aerogel is determined by scanning electron microscopy (SEM) to be 10-200 nm, preferably 50-100 nm.

[0034] Preferably, the average sheet length of the two-dimensional graphene flakes is 0.1-10 μm, preferably 1-5 μm.

[0035] In the present invention, "sheet length" refers to the maximum straight-line distance between two points on the same plane on the sheet, and "sheet thickness" refers to the maximum straight-line distance between two points on a plane perpendicular to the sheet length. The sheet length and sheet thickness of 50 two-dimensional graphene sheets in the graphene aerogel were counted by scanning electron microscopy, and their average values ​​were calculated.

[0036] In the present invention, the surface morphology of the graphene aerogel is observed by a scanning electron microscope (SEM), and the SEM analysis is tested on a S-4800 scanning electron microscope instrument produced by Hitachi, Japan, with a test voltage of 1-10 kV and a magnification of 0.5-50 k.

[0037] The internal structure of the graphene aerogel was characterized by transmission electron microscopy (TEM). The TEM analysis was tested on a TECNAI G2 F20 transmission electron microscope instrument produced by FEI Company of the United States. The test voltage was 100-500 kV and the magnification was 1-100k.

[0038] In the scanning electron microscope image (SEM image), the graphene aerogel has a three-dimensional porous network structure formed by stacking two-dimensional graphene sheets. The sheet sizes are relatively uniform, the stacking is relatively dense, and more connections are formed between the sheets. Further magnification shows that there are abundant pores distributed between the sheets. The internal structure characterized by the transmission electron microscope image (TEM image) shows that a network structure is formed inside the graphene aerogel, which has good dispersibility and is conducive to the transmission of the medium.

[0039] In some preferred embodiments of the present invention, the compressive strength of the graphene aerogel is higher than 30kPa, even up to 80kPa, preferably 40-50kPa. In the present invention, the compressive strength of the graphene aerogel is related to the morphology, pore number and pore structure of the graphene aerogel. By ensuring that the pores with a pore size of less than 20nm are within a certain content range, while ensuring the shuttling of the solution, it helps to improve the compressive strength of the graphene aerogel. Under the above-mentioned preferred compressive strength, it is conducive to the recovery and reuse of the graphene aerogel and reduces losses. The compressive strength of the graphene aerogel in the prior art is generally 10-30kPa.

[0040] In the present invention, the test conditions for the compressive strength of graphene aerogel include: pressing the graphene aerogel to be tested into a cylindrical specimen with a height of 10 mm and a diameter of 10 mm, immersing the prepared specimen in 37°C physiological saline, and then heating it in a constant temperature water bath for 24 hours, using a vernier caliper to accurately measure the individual diameter of each specimen, accurate to 0.02 mm, using a preload of 5N and a loading speed of 1mm / min on an electronic universal testing machine to vertically pressurize the specimen, and record the maximum load value when the specimen breaks. Compression strength P = F / S, where F is the maximum load value when the specimen breaks (N), and S is the bottom area of ​​the cylindrical specimen (mm 2 ), the unit of compressive strength is MPa, which is converted to kPa.

[0041] In some preferred embodiments of the present invention, the method for preparing the graphene aerogel comprises:

[0042] (1) uniformly mixing a dispersion containing graphene oxide and a reducing agent, and performing a reduction reaction to obtain a graphene hydrogel;

[0043] (2) removing the solvent in the graphene hydrogel to obtain a graphene aerogel intermediate product;

[0044] (3) contacting the graphene aerogel intermediate product with an acidic solution to perform an activation reaction.

[0045] According to the present invention, after preparing a graphene aerogel intermediate product by an oxidation-first-reduction method, an acidic solution is used to activate the graphene aerogel intermediate product, so that the graphene aerogel has an appropriate amount of proton acid, a suitable number of pores and a pore structure. When the prepared graphene aerogel is used in the desorption process after the composite amine captures carbon dioxide, it helps to accelerate the CO 2 Desorption.

[0046] In some preferred embodiments of the present invention, the concentration of the dispersion containing graphene oxide is 0.5-10 mg / mL, preferably 1-3 mg / mL. The present invention has no particular limitation on the source of the graphene oxide, which can be commercially available or prepared by a conventional method for preparing graphene oxide in the art. For example, the graphene oxide can be prepared by the Hummers method or the improved Hummers method. The technology for preparing graphene oxide by the Hummers method or the improved Hummers method is well known to those skilled in the art and can be carried out with reference to the prior art.

[0047] In some preferred embodiments of the present invention, the mass ratio of the reducing agent to graphene oxide is 0.001-2:1. In order to make the prepared graphene aerogel have both suitable pore structure and good compressive strength, the mass ratio of the reducing agent to graphene oxide is preferably 0.004-1:1.

[0048] Any reducing agent known in the art that can be used for graphene oxide reduction can be applied to the present invention, for example, ethylenediamine, ascorbic acid, etc. can be used.

[0049] In some preferred embodiments of the present invention, the reducing agent is ethylenediamine. When ethylenediamine is used as a reducing agent, it not only helps to improve the reduction degree of graphene, but also plays a cross-linking role. At the same time, as a weak reducing agent, it can make the final product have a fluffy structure and an appropriate number of pores and pore structure, thereby helping to promote CO 2 In addition, the use of ethylenediamine can enhance the hydrophilicity of the product, thereby eliminating the need for the addition of an additional cross-linking agent, and the resulting graphene aerogel has a strong hydrophilicity.

[0050] In some preferred embodiments of the present invention, in step (1), the reduction reaction temperature is 60-180°C, preferably 80-100°C; and the time is 6-18h, preferably 6-10h.

[0051] In the present invention, there is no particular limitation on the mixing method of the dispersion containing graphene oxide and the reducing agent, and the mixing method may be ultrasonic and / or stirring, as long as the dispersion and the reducing agent can be uniformly mixed.

[0052] In the present invention, any conventional method in the art can be used to remove the solvent in the graphene hydrogel, as long as the solvent in the graphene hydrogel can be effectively removed to obtain a graphene aerogel. For example, the method of removing the solvent in the graphene hydrogel includes: immersing the graphene hydrogel in an aqueous solution of alcohol and then performing a first drying.

[0053] In some preferred embodiments of the present invention, the volume content of alcohol in the alcohol aqueous solution is 10-50%, preferably 20-30%; the alcohol can be a C1-C5 monohydric alcohol, such as at least one of ethanol, methanol, and isopropanol.

[0054] The present invention has no particular limitation on the amount of the alcohol aqueous solution, as long as the graphene hydrogel can be completely immersed.

[0055] According to the present invention, there may be multiple ways of the first drying. In some specific embodiments of the present invention, the first drying includes: first freezing at -10 to -30°C for 1-12h, and then freeze drying at -40 to -120°C for 24-60h. In the present invention, by using ethylenediamine as a reducing agent and controlling the temperature gradient of the first drying, it is possible to ensure that the graphene aerogel has an appropriate number of pores and pore structure, and to ensure the stability of the internal structure of the graphene aerogel, thereby improving the compressive strength of the graphene aerogel. Preferably, the first drying includes: first freezing at -15 to -25°C for 1-5h, and then freeze drying at -50 to -90°C for 24-36h.

[0056] In the present invention, the graphene aerogel intermediate product is activated by an acidic solution, so that the graphene aerogel has an appropriate amount of proton acid, which provides an acidic site for the desorption of the alcohol amine solution that absorbs carbon dioxide. In some specific embodiments of the present invention, the acidic solution is provided by an aqueous solution of an acid. The present invention has a wide range of selection for the specific type of the acid, and can use conventional organic acids or inorganic acids in the art, such as at least one of nitric acid, hydrochloric acid, sulfuric acid, oxalic acid and acetic acid. Preferably, the acid is selected from nitric acid and / or hydrochloric acid.

[0057] In some preferred embodiments of the present invention, the concentration of the aqueous solution of the acid is 4-10 mol / L, preferably 5-8 mol / L.

[0058] In some specific embodiments of the present invention, in order to make the prepared graphene aerogel have a suitable B acid content, the volume ratio of the acidic solution to the graphene aerogel intermediate product is 1-2.5:1, preferably 1-2:1, and more preferably 1-1.5:1.

[0059] In some preferred embodiments of the present invention, the temperature of the activation reaction is 40-90°C, preferably 60-80°C; the time of the activation reaction is 2-8h, preferably 2-4h; the use of the above preferred embodiments helps to retain more active sites without destroying the graphene aerogel structure.

[0060] In some preferred embodiments of the present invention, in order to promote sufficient contact between the graphene aerogel intermediate product and the acidic solution and increase the activation reaction rate, the activation reaction is carried out under stirring conditions.

[0061] In some preferred embodiments of the present invention, the preparation method further comprises: washing and second drying the product obtained by the activation reaction. The washing and second drying can be carried out under conventional operating conditions in the art, as long as the residual acidic solution in the product is removed, and the present invention has no particular limitation on this. Preferably, the temperature of the second drying is 60-120°C, preferably 100-120°C, and the time is 8-24h, preferably 10-15h.

[0062] The second aspect of the present invention provides a regenerated catalyst, which includes a carrier and a metal component loaded on the carrier; the metal component has Lewis acid properties, and the carrier is the graphene aerogel described in the first aspect.

[0063] According to the present invention, a metal component having Lewis acid properties is loaded on the graphene aerogel, so that the regenerated catalyst can not only provide the proton acid necessary for the desorption process, but also provide the necessary basic groups to promote the desorption reaction, thereby fundamentally reducing the energy consumption of the reaction. In the present invention, the metal component is combined with the graphene aerogel through a chemical bond, which is conducive to improving the interaction between the carrier and the metal component, and the single-center adsorption and desorption is changed to multi-center adsorption and desorption, further improving the adsorption and desorption capacity.

[0064] In the present invention, the term "Lewis acid" refers to a molecule or ion that can accept external electrons. The metal component with Lewis acid properties is chemically bonded to the graphene aerogel and can simultaneously provide Lewis acid in the regenerated catalyst.

[0065] In some preferred embodiments of the present invention, the regenerated catalyst comprises B acid and L acid, and the content of B acid is 0.0005-0.02 mmol / g, and more preferably 0.008-0.016 mmol / g.

[0066] In some preferred embodiments of the present invention, the ratio of L acid to B acid in the regenerated catalyst can be regulated by controlling the loading amount of the metal component. In order to improve the desorption performance of the product, preferably, in the regenerated catalyst, the molar ratio of B acid to L acid is 0.01-1:1, preferably 0.1-0.5:1, and more preferably 0.1-0.2:1. Regulating the molar ratio of L acid to B acid within the above preferred range is conducive to improving the desorption efficiency and reducing energy consumption.

[0067] In the present invention, the B acid, L acid and their relative contents in the regenerated catalyst are measured by pyridine infrared method, which is the same as the method mentioned above and will not be described again.

[0068] In some preferred embodiments of the present invention, based on the total mass of the regenerated catalyst, the content of the carrier is 30-70wt%, preferably 30-50wt%; in terms of oxide, the content of the metal component is 30-70wt%, preferably 50-70wt%. Within the above preferred component content range, the regenerated catalyst has pH, which can not only provide the proton acid necessary for the desorption process, but also provide the necessary basic groups, which helps to promote the desorption reaction.

[0069] In the present invention, the content of each component in the regenerated catalyst is obtained by XPS testing.

[0070] The present invention has a wide range of selection for the specific types of the metal components, and all metals with Lewis acid properties can be applied to the present invention. In some preferred embodiments of the present invention, the metal component is selected from transition metal elements and / or Group IIIA elements, preferably at least one of Fe, Mn, Co, Ni, Cu, Zn, La, Ce, Zr, Mo, W, Au, Ag, Ti, Pt, Rh, Ru, Re, Al, Ga and In. In order to further improve the catalytic activity of the regenerated catalyst, improve CO 2 Desorption rate, preferably, the metal component is selected from at least one of Al, Fe, Co, Ni and Ti.

[0071] In the present invention, the metal component is at least partially present in the form of an oxide.

[0072] In some preferred embodiments of the present invention, the regenerated catalyst has a suitable specific surface area. Preferably, the specific surface area of ​​the regenerated catalyst is 30-100 m 2 / g, preferably 45-80m 2 In the above preferred case, the regenerated catalyst has a good dispersion effect, which is conducive to the exposure of more active sites and accelerates the reaction.

[0073] In some preferred embodiments of the present invention, the total pore volume of the regenerated catalyst is 0.06-0.2 mL / g, preferably 0.1-0.15 mL / g. The rich pore distribution inside the regenerated catalyst can not only ensure the mass transfer efficiency and improve the regeneration efficiency, but also have a high mechanical strength and increase the service life of the catalyst.

[0074] In some preferred embodiments of the present invention, in the regenerated catalyst, the volume of pores with a pore size of less than 20 nm accounts for no less than 30% of the total pore volume of the regenerated catalyst, preferably 30-80%, and more preferably 50-60%. Compared with unloaded graphene aerogel, after the catalyst is prepared by loading the metal component, the volume proportion of pores with a pore size of less than 20 nm is reduced. The reason may be that part of the metal component fills the pores with a pore size of less than 20 nm in the graphene aerogel, thereby reducing this part of the pores. In this case, the metal component is anchored on the graphene aerogel, which is conducive to exerting the activity of the metal component. The combination with an appropriate amount of B acid can improve the catalytic efficiency, thereby reducing the desorption temperature and shortening the desorption time, and helping to reduce the catalyst loss rate during the regeneration process of the alcohol amine solution, and extending the service life of the catalyst.

[0075] In the present invention, the specific surface area, pore volume and pore distribution of the regenerated catalyst are determined by N 2 Measured by adsorption-desorption isotherm method.

[0076] According to a preferred embodiment of the present invention, the method for preparing the regenerated catalyst comprises:

[0077] S1. In the presence of ultrasound, a carrier and a solution of a soluble compound containing a metal component are mixed to obtain a mixed solution;

[0078] S2, adding a precipitant to the mixed solution to carry out a precipitation reaction, followed by drying and calcining;

[0079] Wherein, the carrier includes the graphene aerogel described in the first aspect, and the metal component has Lewis acid properties.

[0080] According to the present invention, the metal component can be loaded on the carrier by in-situ deposition through the impregnation-precipitation method, so that in the prepared regenerated catalyst, the metal component is bonded to the graphene aerogel through chemical bonds, and the metal component and the carrier have a strong interaction, which helps to improve the catalytic activity of the regenerated catalyst and improve CO 2 Desorption rate.

[0081] In some preferred embodiments of the present invention, in step S1, the volume ratio of the solution of the soluble compound containing the metal component to the carrier is 0.1-4:1, preferably 0.5-2:1.

[0082] In the present invention, the concentration of the solution of the soluble compound containing the metal component has a wide selection range. In order to ensure uniform dispersion of the metal oxide and avoid clogging of the pores, preferably, the concentration of the solution of the soluble compound containing the metal component is 0.5-2 mol / L, and more preferably 1-1.5 mol / L.

[0083] In some preferred embodiments of the present invention, the frequency of the ultrasonic wave is 10000-100000 Hz, preferably 30000-50000 Hz; the mixing time is 1-3 hours, preferably 1-1.5 hours. The above preferred mixing method is helpful for uniform mixing and sufficient contact between the carrier and the soluble compound of the metal component, which is beneficial to improve the uniformity and dispersion of the metal component loaded on the carrier.

[0084] In the present invention, there is no particular limitation on the specific type of the soluble compound of the metal component, and it can be selected from conventional soluble organic salts or inorganic salts containing metal components in the art, for example, it can be selected from at least one of nitrates, acetates, sulfates and chlorides containing metal components.

[0085] The present invention has a wide range of selection for the specific types of the metal components, and all metals with Lewis acid properties can be applied to the present invention. In some preferred embodiments of the present invention, the metal component is selected from transition metal elements and / or Group IIIA elements, preferably at least one of Fe, Mn, Co, Ni, Cu, Zn, La, Ce, Zr, Mo, W, Au, Ag, Ti, Pt, Rh, Ru, Re, Al, Ga and In. In order to further improve the catalytic activity of the regenerated catalyst, improve CO 2 Desorption rate, preferably, the metal component is selected from at least one of Al, Fe, Co, Ni and Ti.

[0086] In some preferred embodiments of the present invention, in step S2, the pH of the precipitation reaction is adjusted by adding a precipitant. Preferably, the pH of the precipitation reaction is 8-10, preferably 8-9.

[0087] In some preferred embodiments of the present invention, the addition rate of the precipitant is 0.1-2 mL / min, preferably 0.5-1 mL / min, relative to 1 L of the mixed solution. Controlling the addition rate of the precipitant within the above preferred range is conducive to more uniform precipitation of metal ions.

[0088] The present invention has no particular limitation on the specific selection of the precipitant, and conventional precipitants in the art can be applied to the present invention. For example, the precipitant can be ammonia water. The present invention has a wide range of selection for the concentration of the ammonia water, preferably, the concentration of the ammonia water is 22-28wt%.

[0089] In the present invention, there is no particular limitation on the specific method and conditions of drying in step S2, as long as the solvent in the product of the precipitation reaction can be removed. A solid-liquid separation operation may also be included before the drying, and the present invention does not have any particular limitation on the specific method of the solid-liquid separation, and those skilled in the art may select it according to actual needs.

[0090] In some preferred embodiments of the present invention, in step S2, the drying temperature is 40-150° C., and the drying time is 8-24 h; preferably, the drying temperature is 80-120° C., and the drying time is 8-12 h.

[0091] In some preferred embodiments of the present invention, in step S2, the calcination temperature is 300-1000°C, preferably 300-600°C; the calcination time is 1-10h, preferably 4-8h.

[0092] The third aspect of the present invention provides the regenerated catalyst according to the second aspect in a CO-rich 2 Application in the regeneration of amine solutions.

[0093] The regenerated catalyst can be used as a CO 2 Desorption catalysts for CO-rich 2 During the regeneration of the amine solution, the CO-rich 2 Amine solution refers to the absorption of CO 2 The organic amine solution can be any known organic amine solution for CO 2 The absorbed organic amine or composite organic amine solution includes, but is not limited to, a combination of one or more of monoethanolamine, diethanolamine, methyldiethanolamine, and triethanolamine.

[0094] The graphene aerogel B acid content, suitable pore number and pore structure in the regeneration catalyst, in synergistic effect with the metal component, is applied to CO-rich 2 During the regeneration process of the amine solution, the desorption reaction can be effectively promoted, which is beneficial to the catalytic CO 2 Desorption, reduce the initial and end temperatures of desorption, increase the desorption rate, shorten the desorption time, reduce the desorption energy consumption and increase the desorption amount. In addition, the regenerated catalyst has high mechanical strength, thereby increasing the cycle life.

[0095] A fourth aspect of the present invention provides a CO-rich 2 A method for regenerating an amine solution, under regeneration conditions, 2 The amine solution is contacted with the catalyst to produce CO 2 Desorption;

[0096] Wherein, the catalyst is the regenerated catalyst described in the second aspect.

[0097] In some preferred embodiments of the present invention, the CO-rich 2 Based on the total mass of the amine solution, the amount of the catalyst is 1-10wt%, preferably 1-3wt%.

[0098] Conventional regeneration catalysts in the prior art are used for CO-rich 2 When the amine solution is regenerated, the preparation cost of the regenerated catalyst is high, and the required initial desorption temperature is high and the reaction time is long, which leads to high energy consumption in the desorption process. The regenerated catalyst provided by the present invention uses graphene aerogel as a carrier, which, under the synergistic effect with the metal component, is conducive to promoting the desorption reaction in the positive direction, greatly reducing the desorption temperature and desorption energy consumption, and the loss rate of the catalyst in the repeated regeneration process is low, which is conducive to improving the CO2-rich 2 Economics of amine solution regeneration.

[0099] The reason may be that graphene aerogel has an appropriate amount of proton acid (B acid), a suitable number of pores and a pore structure, which is conducive to the catalysis of CO 2 Desorption, reduce the initial and end temperatures of desorption, increase the desorption rate, thereby reducing the desorption energy consumption, and further load the metal components to provide proton acid and a certain weak base for the carbon dioxide desorption process, thereby promoting the rich CO 2 The breakage of MEA-COO- and the deprotonation process of MEAH+ in the amine solution; at the same time, the appropriate number of pores and pore structure of graphene aerogel are also beneficial to improving the mechanical strength of the catalyst, which helps to anchor the metal components during the catalyst preparation process, thereby reducing the loss of the catalyst and increasing the service life of the regenerated catalyst, which is beneficial to industrial application.

[0100] In some preferred embodiments of the present invention, the CO 2 The initial temperature of desorption is 10-70° C., preferably 30-50° C. According to the present invention, the desorbed CO is recorded during the regeneration process. 2 The accumulated volume flow rate is constant, indicating that the regeneration is over. The initial temperature refers to the CO 2 The temperature at which desorption begins, and the time from the start of desorption to the end of regeneration is recorded as the regeneration time.

[0101] According to the present invention, the CO-rich 2 The regeneration of amine solution has a lower initial temperature and a higher desorption rate, which further reduces the CO rich 2 The regeneration energy consumption of the amine solution and the loss rate of the regenerated catalyst are low, which is conducive to the industrial application of the chemical absorption method.

[0102] In some preferred embodiments of the present invention, in order to make the CO-rich 2The amine solution is fully in contact with the catalyst to further accelerate the desorption rate. 2 The contact between the amine solution and the catalyst is carried out under stirring conditions, and the stirring rate is preferably 100-200 rpm.

[0103] In the present invention, the CO-rich 2 Amine solution refers to the absorption of CO 2 The organic amine solution can be any known organic amine solution for CO 2 The organic amine or composite organic amine solution to be absorbed, and the selection range of the organic amine solution have been described in the foregoing text, which will not be repeated here.

[0104] The present invention will be described in detail below through examples.

[0105] The graphene used in the following preparation examples and embodiments is a commercially available product of Qingdao Huatai Lubrication and Sealing Technology Co., Ltd., and the composite amine solution is purchased from Sinopec Nanjing Chemical Research Institute, model number MA-2.

[0106] Unless otherwise specified, the raw materials used were purchased from commercial sources.

[0107] The test methods involved in the embodiments are as follows:

[0108] (1) The contents of B acid and L acid were determined by pyridine infrared method. The specific test method was as follows: 0.0089 g of the sample to be tested was pressed into a self-supporting sheet with a diameter of 1.3 cm and placed in an in-situ cell. The sample was evacuated at 300 °C and cooled to room temperature to measure the background infrared spectrum. The saturated vapor of pyridine was adsorbed until the sample was saturated with adsorption and the spectrum was recorded. After He purging for 1 h, the sample was evacuated and programmed temperature desorption (0-350 °C) was performed and the spectrum was recorded every 20 °C. The standard positions of B acid and L acid in the pyridine infrared spectrum were 1540 cm -1 and 1450cm -1 , integrate the peaks at the corresponding positions in the graph, and normalize the peak area of ​​the spectrum to calculate the relative acid value. The acid value is calculated according to the following formula.

[0109]

[0110] Wherein, C is the acid content, unit, mmol / g; K L / B is the absorption coefficient of L acid or B acid, which are 1.42 and 1.88 respectively, that is, K L is the absorption coefficient of L acid, which is 1.42, K B is the absorption coefficient of B acid, which is 1.88, and the unit is mmol / cm; I L / B is the peak area of ​​L acid or B acid, in cm -1; R is the tablet diameter, in cm; W is the tablet weight, in g.

[0111] (2) Specific surface area, pore volume, and pore size distribution tests

[0112] Specific surface area, pore volume and pore structure distribution were measured by N 2 Measured by adsorption-desorption isotherm method.

[0113] (3) X-ray photoelectron spectroscopy (XPS) analysis was performed on an ESCALAB250XI X-ray photoelectron spectrometer produced by Thermo Fisher Scientific Inc., USA. The test conditions included: the excitation source was Al Kα ray, and the scanning range was 0-1200 eV.

[0114] (4) Scanning electron microscope (SEM) test

[0115] Scanning electron microscope analysis was tested on a S-4800 scanning electron microscope produced by Hitachi, Japan, with a test voltage of 1-10 kV and a magnification of 0.5-50 k.

[0116] (5) Transmission electron microscopy (TEM) test

[0117] Transmission electron microscope analysis was tested on a TECNAI G2 F20 transmission electron microscope instrument produced by FEI Company of the United States, with a test voltage of 100-500 kV and a magnification of 1-5000 k.

[0118] (6) Compression strength test

[0119] The graphene aerogel to be tested was pressed into a cylindrical specimen with a height of 10 mm and a diameter of 10 mm. The prepared specimen was immersed in 37°C physiological saline, and then heated in a constant temperature water bath for 24 hours. The individual diameter of each specimen was accurately measured with a vernier caliper, accurate to 0.02 mm. The specimen was vertically pressurized with a preload of 5 N and a loading speed of 1 mm / min on an electronic universal testing machine, and the maximum load value when the specimen broke was recorded. The compressive strength P = F / S, where F is the maximum load value when the specimen breaks (N), and S is the bottom area of ​​the cylindrical specimen (mm 2 ), the unit of compressive strength is MPa, which is converted to kPa.

[0120] The following preparation example is used to illustrate the preparation of graphene aerogel.

[0121] Preparation Example 1

[0122] (1) Preparation of graphene oxide: 0.6 g of graphene, 3 g of potassium permanganate, 30 mL of concentrated sulfuric acid (98 wt%), and the reactor shell and tetrafluoroethylene liner were placed in a 4 ° C refrigerator for 8 h. The refrigerated graphite, potassium permanganate and concentrated sulfuric acid were poured into the reactor, and the reactor was quickly covered and the lid was tightened. The reactor was placed in an ice bath, the temperature was controlled at 4 ° C and allowed to stand for 1.5 hours, and then placed in an 80 ° C oven for 1.5 hours to react and then taken out and cooled to room temperature. The reaction product was slowly poured into deionized water and stirred and diluted, and the volume of water was 5 times the volume of concentrated sulfuric acid. 5 mL of hydrogen peroxide was added dropwise while stirring until the mixture was yellow-brown or golden yellow. Let it stand for 24 hours, pour off the supernatant, and centrifuge the bottom precipitate. The centrifuged product was washed 5 times with 5 wt% hydrochloric acid solution and deionized water respectively until the pH was > 5, and then transferred to a centrifuge, centrifuged at 1000 rpm for 15 minutes, and the supernatant was poured off. The middle and lower layer samples were poured into a beaker, diluted with water and washed, and then centrifuged, and repeated 4 times until the pH was > 5. After washing, the middle and lower layer slurry was transferred to a light-proof container and stored in a refrigerator at 4°C.

[0123] (2) Use a dropper to measure the graphene oxide slurry prepared above, add water to dilute, and obtain 2 mg / mL GO slurry. Mix the GO slurry and ethylenediamine at a mass ratio of ethylenediamine to graphene oxide of 0.004:1, stir ultrasonically, pour into a glass bottle, and heat at 95°C for 6 h for chemical reduction. Cool to room temperature, and take out the solid in the kettle, which is the graphene hydrogel GH.

[0124] (3) Soak the prepared GH in 150 mL of 20% V / V ethanol aqueous solution, transfer it to a centrifuge tube, and place it in the freezer of a refrigerator at a temperature of about -20°C for 1 hour. Place the frozen GH in a freeze dryer, set the temperature to -90°C, evacuate, and keep it for 24 hours. Obtain a graphene aerogel intermediate product.

[0125] (4) The graphene aerogel intermediate product was dissolved in an equal volume of dilute nitric acid solution (concentration of 8 mol / L), heated to 80°C, stirred and reacted for 2 hours. After the reaction was completed, the graphene was taken out, washed with clean water until neutral, and placed in an oven at 100°C to dry for 12 hours. Graphene aerogel A1 was obtained.

[0126] The surface morphology of graphene aerogel A1 was observed by scanning electron microscopy (SEM). Figure 1 As shown, the graphene aerogel is a three-dimensional porous network structure formed by stacking two-dimensional graphene sheets, the sheet size is relatively uniform, the stacking is relatively dense, more connections are formed between the sheets, and there are abundant pores between the sheets. The average sheet length is 2.5μm, and the average sheet thickness is 50nm.

[0127] The internal structure of graphene aerogel A1 was characterized by transmission electron microscopy (TEM), such as Figure 2 As shown, a network structure is formed inside the graphene aerogel, which has good dispersibility and is conducive to the transmission of the medium.

[0128] X-ray photoelectron spectroscopy (XPS) was used to characterize the chemical composition of graphene aerogel A1, such as Figure 3 As shown, it is proved that the prepared graphene aerogel contains C element, N element and O element. The molar ratio of C element, O element and N element is determined to be approximately 25:6:1 through the area of ​​the corresponding peaks in the X-ray photoelectron energy spectrum.

[0129] like Figure 4 As shown, the spectrum of O1s in the X-ray photoelectron spectrum of the graphene aerogel proves that the oxygen species in the graphene aerogel include hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen is determined to be 4:1.5:1 by the peak area of ​​the peak separation.

[0130] By N 2 Adsorption-desorption isotherms were used to test the specific surface area, total pore volume and pore size distribution of graphene aerogel A1. Figure 5 As shown, it can be seen that its pore size distribution is concentrated below 20 nm.

[0131] The B acid content of graphene aerogel A1 was determined by pyridine infrared method, and the compressive strength of A1 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0132] Preparation Example 2

[0133] (1) Preparation of graphene oxide: 0.6 g of graphene, 4.0 g of potassium permanganate, 40 mL of concentrated sulfuric acid (98 wt%), and the reactor shell and tetrafluoroethylene lining were placed in a 4 ° C refrigerator for 12 h. The refrigerated graphite, potassium permanganate and concentrated sulfuric acid were poured into the reactor, and the reactor was quickly covered and the lid was tightened. The reactor was placed in an ice bath, the temperature was controlled at 4 ° C and allowed to stand for 3 hours, and then placed in an 80 ° C oven for 3 hours and then taken out and cooled to room temperature. The reaction product was slowly poured into deionized water and stirred and diluted, and the volume of water was 5 times the volume of concentrated sulfuric acid. 5 mL of hydrogen peroxide was added dropwise while stirring until the mixture was yellow-brown or golden yellow. Let it stand for 24 hours, pour off the supernatant, and centrifuge the bottom precipitate. The centrifuged product was washed 5 times with 5% hydrochloric acid solution and deionized water respectively until the pH was > 5, and then transferred to a centrifuge, centrifuged at 1000 rpm for 15 minutes, and the supernatant was poured off. The middle and lower layer samples were poured into a beaker, diluted with water and washed, and then centrifuged, and repeated 4 times until the pH was > 5. After washing, the middle and lower layer slurry was transferred to a light-proof container and stored in a refrigerator at 4°C.

[0134] (2) Use a dropper to measure the graphene oxide slurry prepared above, add water to dilute, and obtain 2 mg / mL GO slurry. Mix the GO slurry and ethylenediamine in a mass ratio of ethylenediamine to graphene oxide of 1:1, stir ultrasonically, pour into a glass bottle, heat at 90°C for 8h for chemical reduction. Cool to room temperature, and take out the solid in the kettle, which is the graphene hydrogel GH.

[0135] (3) Soak the prepared GH in 150 mL of 20% V / V ethanol aqueous solution, transfer it to a centrifuge tube, and place it in the freezer of a refrigerator at a temperature of about -25°C for 1 hour. Place the frozen GH in a freeze dryer, set the temperature to -60°C, evacuate, and keep it for 20 hours. Obtain a graphene aerogel intermediate product.

[0136] (4) The graphene aerogel intermediate product was dissolved in an equal volume of dilute nitric acid solution (concentration of 6 mol / L), heated to 70°C, stirred and reacted for 4 hours. After the reaction was completed, the graphene was taken out, washed with clean water until neutral, and placed in an oven at 100°C for 12 hours to obtain graphene aerogel A2.

[0137] The surface morphology of graphene aerogel A2 was observed by scanning electron microscopy (SEM). Figure 1 similar.

[0138] The chemical composition of the graphene aerogel A2 was characterized by X-ray photoelectron spectroscopy (XPS), and the molar ratio of the C element, the O element, and the N element was 15:12:2.

[0139] The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 3:1.5:1 by the peak area of ​​O1s peak.

[0140] By N 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel A2 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A2 was determined by pyridine infrared method. The compressive strength of A2 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0141] Preparation Example 3

[0142] (1) Graphene oxide was prepared according to the method in Preparation Example 1.

[0143] (2) Use a dropper to measure the graphene oxide slurry prepared above, add water to dilute, and obtain 2 mg / mL GO slurry. Mix the GO slurry and ethylenediamine at a mass ratio of ethylenediamine to graphene oxide of 0.01:1, stir ultrasonically, pour into a glass bottle, and heat at 80°C for 10 h for chemical reduction. Cool to room temperature, and take out the solid in the kettle, which is the graphene hydrogel GH.

[0144] (3) Soak the prepared GH in 150 mL of 20% V / V ethanol aqueous solution, transfer it to a centrifuge tube, and place it in the freezer of a refrigerator at a temperature of about -15°C for 1 hour. Place the frozen GH in a freeze dryer, set the temperature to -50°C, evacuate, and keep it for 24 hours. Obtain a graphene aerogel intermediate product.

[0145] (4) The graphene aerogel intermediate product was dissolved in an equal volume of dilute hydrochloric acid solution (concentration of 5 mol / L), heated to 60°C, stirred and reacted for 2 hours. After the reaction was completed, the graphene was taken out, washed with clean water until neutral, and placed in an oven at 120°C for 16 hours to obtain graphene aerogel A3.

[0146] The surface morphology of graphene aerogel A3 was observed by scanning electron microscopy (SEM). Figure 1 similar.

[0147] The chemical composition of graphene aerogel A3 was characterized by X-ray photoelectron spectroscopy (XPS), and the molar ratio of C, O and N was about 25:15:2. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 3:1:1 by the peak area of ​​O1s peak separation.

[0148] By N 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel A3 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A3 was determined by pyridine infrared method. The compressive strength of A3 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0149] Preparation Example 4

[0150] The method in Preparation Example 1 is used, except that step (2) includes: using a dropper to measure the graphene oxide slurry prepared above, adding water to dilute to obtain 2 mg / mL GO slurry, mixing the GO slurry and ethylenediamine at a mass ratio of ethylenediamine to graphene oxide of 0.001:1, ultrasonically stirring, pouring into a glass bottle, heating at 90°C for 6 hours for chemical reduction. Cooling to room temperature, taking out the solid in the kettle, that is, graphene hydrogel GH.

[0151] The prepared graphene aerogel is recorded as A4.

[0152] The surface morphology of graphene aerogel A4 was observed by scanning electron microscopy (SEM). Figure 1 similar;

[0153] The chemical composition of graphene aerogel A4 was characterized by X-ray photoelectron spectroscopy (XPS), and the molar ratio of C, O and N was 45:5:1. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 7.5:1.5:1 by the peak area of ​​O1s peak separation.

[0154] By N 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel A4 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A4 was determined by pyridine infrared method. The compressive strength of A4 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0155] Preparation Example 5

[0156] The method in Preparation Example 1 was followed, except that an equal amount of ascorbic acid was used to replace ethylenediamine, to obtain graphene aerogel A5.

[0157] The surface morphology of graphene aerogel A5 was observed by scanning electron microscopy (SEM). Figure 1 similar;

[0158] The chemical composition of graphene aerogel A5 was characterized by X-ray photoelectron spectroscopy (XPS), and the molar ratio of C, O and N was 40:3. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 10:2:1 by the peak area of ​​O1s peak separation.

[0159] By N 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel A5 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A5 was determined by pyridine infrared method. The compressive strength of A5 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0160] Preparation Example 6

[0161] The method in Preparation Example 1 is used, except that step (4) includes: dissolving the graphene aerogel intermediate product in an equal volume of dilute nitric acid solution (concentration of 4 mol / L), heating to 80°C, stirring and reacting for 2 hours, and after the reaction, taking out the graphene, washing it with clean water until it is neutral, and drying it in an oven at 100°C for 12 hours. Graphene aerogel A6 is obtained.

[0162] The surface morphology of graphene aerogel A6 was observed by scanning electron microscopy (SEM). Figure 1 similar.

[0163] The chemical composition of graphene aerogel A6 was characterized by X-ray photoelectron spectroscopy (XPS). The molar ratio of C, O and N was 30:5:0.3. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 6:1.5:1 by the peak area of ​​O1s peak separation. 2The specific surface area, total pore volume and pore size distribution of graphene aerogel A6 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A6 was determined by pyridine infrared method. The compressive strength of A6 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0164] Preparation Example 7

[0165] The method in Preparation Example 1 is used, except that step (4) includes: dissolving the graphene aerogel intermediate product in an equal volume of dilute nitric acid solution (concentration of 1 mol / L), heating to 60°C, stirring and reacting for 2 hours, and after the reaction, taking out the graphene, washing it with clean water until it is neutral, and drying it in an oven at 100°C for 12 hours. Graphene aerogel A7 is obtained.

[0166] The surface morphology of graphene aerogel A7 was observed by scanning electron microscopy (SEM). Figure 1 similar;

[0167] The chemical composition of graphene aerogel A7 was characterized by X-ray photoelectron spectroscopy (XPS). The molar ratio of C, O and N was 35:4:0.3. The molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen was determined to be 6.5:1:0.5 by the peak area of ​​O1s peak separation. 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel A7 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel A7 was determined by pyridine infrared method. The compressive strength of A7 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0168] Comparative Preparation Example 1

[0169] The graphene aerogel intermediate product obtained in step (3) of Preparation Example 1 is recorded as graphene aerogel DA1.

[0170] Scanning electron microscopy (SEM) observation showed that the surface morphology of graphene aerogel DA1 was a porous structure composed of graphene sheets.

[0171] X-ray photoelectron spectroscopy (XPS) was used to characterize the chemical composition of graphene aerogel DA1, and the molar ratio of C, N and O was determined to be 25:6:1. The peak area of ​​the O1s peak determined that the graphene aerogel only contained hydroxyl groups.

[0172] By N 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel DA1 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel DA1 was determined by pyridine infrared method. The compressive strength of DA1 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0173] Comparative Preparation Example 2

[0174] The method of Preparation Example 1 is followed, except that step (3) comprises: soaking the prepared GH in 150 mL of 20% V / V ethanol aqueous solution, transferring the prepared GH into a centrifuge tube, placing the prepared GH into a freezer at a temperature of about -10°C for 1 hour. The frozen GH is placed into a freeze dryer at a temperature of -30°C, vacuuming the mixture, and maintaining the mixture for 24 hours. A graphene aerogel intermediate product is obtained.

[0175] Then, the graphene aerogel DA2 was obtained by acid activation according to the method of Preparation Example 1. 2 The specific surface area, total pore volume and pore size distribution of graphene aerogel DA2 were tested by adsorption-desorption isotherms. The B acid content of graphene aerogel DA2 was determined by pyridine infrared method. The compressive strength of DA2 was determined by electronic universal testing machine. The test results are shown in Table 1.

[0176] Table 1

[0177]

[0178] The following examples are used to illustrate the preparation of the regenerated catalyst.

[0179] Example 1

[0180] S1. Place a certain volume of aluminum nitrate solution (with a concentration of 1 mol / L) and graphene aerogel A1 in an ultrasonic wave, wherein the volume ratio of the aluminum nitrate solution to the graphene aerogel is 1:1, and ultrasonicate at 40000 Hz for 1 h to fully mix the two to obtain a mixed solution;

[0181] S2, add 25wt% ammonia water to the above-mentioned mixed solution and stir continuously until the pH is 8-9, and the rate of adding ammonia water is 0.5mL / min relative to 1L of the mixed solution. Filter the product and place it in a drying oven, dry it at 110℃ for 8h, and then place it in a muffle furnace and calcine it at 400℃ for 6h to obtain regenerated catalyst S1. Based on the total mass of the regenerated catalyst, the content of the carrier is 40wt%; the content of aluminum oxide is 60wt%.

[0182] The surface morphology of the regenerated catalyst S1 was observed by scanning electron microscopy (SEM). The loaded catalyst still had a three-dimensional porous network structure formed by stacking two-dimensional graphene sheets, and the pore structure on the surface of the graphene sheet remained relatively intact. The catalyst maintained the looseness of the graphene aerogel, and the aerogel did not agglomerate after loading, indicating that it still had good dispersibility, which was conducive to the transfer of the medium.

[0183] By N 2The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S1 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S1 were determined by pyridine infrared method. The test results are shown in Table 2.

[0184] Example 2

[0185] S1, placing a certain volume of ferric nitrate solution (concentration of 1 mol / L) and graphene aerogel A2 in an ultrasonic wave, with the volume ratio of ferric nitrate solution to graphene aerogel being 1:1, and ultrasonicating at 40000 Hz for 10 h to fully mix the two to obtain a mixed solution;

[0186] S2, add 25wt% ammonia water to the above-mentioned mixed solution and stir continuously until the pH is 8-9, and the rate of adding ammonia water is 1mL / min relative to 1L of the mixed solution. After filtering the product, place it in an oven at 100°C for 12h, dry it at room temperature, and then place it in a muffle furnace for calcination at 550°C for 6h to obtain regenerated catalyst S2. Based on the total mass of the regenerated catalyst, the content of the carrier is 31wt%; the content of ferrosoferric oxide is 69wt%.

[0187] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S2 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S2 were determined by pyridine infrared method. The test results are shown in Table 2.

[0188] Example 3

[0189] S1. Place a certain volume of cobalt nitrate solution (prepared with a concentration of 1 mol / L) and graphene aerogel A3 in an ultrasonic chamber, and ultrasonicate at 40000 Hz for 1 h in a volume ratio of cobalt nitrate solution to graphene aerogel of 1:1 to fully mix the two to obtain a mixed solution;

[0190] S2, add 25wt% ammonia water to the above-mentioned mixed solution and stir continuously until the pH is 8-9. The rate of adding ammonia water is 0.5mL / min relative to 1L of the mixed solution. After filtering the product, place it in an oven at 110℃ for 8h, dry it at room temperature, and then place it in a muffle furnace for calcination at 400℃ for 6h to obtain regenerated catalyst S3. Based on the total mass of the regenerated catalyst, the content of the carrier is 48wt%; the content of cobalt oxide is 52wt%. By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S3 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S3 were determined by pyridine infrared method. The test results are shown in Table 2.

[0191] Example 4

[0192] S1, placing a certain volume of ferric nitrate solution (concentration 1.0 mol / L) and graphene aerogel A2 in an ultrasonic wave, with the volume ratio of ferric nitrate solution to graphene aerogel being 1:1, and ultrasonicating at 40000 Hz for 10 h to fully mix the two to obtain a mixed solution;

[0193] S2, after filtering the product, place it in an oven at 110°C for 12 hours, dry it at room temperature, and then place it in a muffle furnace for calcination at 650°C for 4 hours to obtain a regenerated catalyst S4. Based on the total mass of the regenerated catalyst, the content of the carrier is 31wt%; the content of ferric oxide is 69wt%. When the precipitant is not introduced, a higher calcination temperature is required to ensure the loading of the metal oxide, which may cause the graphene aerogel to agglomerate, and the specific surface area and pore volume are reduced.

[0194] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S4 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S4 were determined by pyridine infrared method. The test results are shown in Table 2.

[0195] Example 5

[0196] The method in Example 1 was followed, except that graphene aerogel A4 was used instead of A1 to obtain regenerated catalyst S5.

[0197] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S5 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S5 were determined by pyridine infrared method. The test results are shown in Table 2.

[0198] Example 6

[0199] The method in Example 1 was followed, except that graphene aerogel A5 was used instead of A1 to obtain regenerated catalyst S6.

[0200] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S6 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S6 were determined by pyridine infrared method. The test results are shown in Table 2.

[0201] Example 7

[0202] The method in Example 1 was followed, except that graphene aerogel A6 was used instead of A1 to obtain regenerated catalyst S7.

[0203] By N 2The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S7 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S7 were determined by pyridine infrared method. The test results are shown in Table 2.

[0204] Example 8

[0205] The method in Example 1 was followed, except that graphene aerogel A7 was used instead of A1 to obtain regenerated catalyst S8.

[0206] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S8 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S8 were determined by pyridine infrared method. The test results are shown in Table 2.

[0207] Example 9

[0208] The method of Example 1 is followed, except that the aluminum nitrate solution is replaced with a boric acid solution of equal concentration and volume to obtain a regenerated catalyst S9.

[0209] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst S9 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst S9 were determined by pyridine infrared method. The test results are shown in Table 2.

[0210] Comparative Example 1

[0211] According to the mass ratio of aluminum oxide to graphene aerogel A1 being 2:3, commercially available aluminum oxide and graphene aerogel A1 were physically ground and then calcined at 400° C. for 6 h in a muffle furnace to obtain a regenerated catalyst DS1.

[0212] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst DS1 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst DS1 were determined by pyridine infrared method. The test results are shown in Table 2.

[0213] Comparative Example 2

[0214] The method in Example 1 was followed, except that an equal amount of HZSM-5 molecular sieve (commercially available, Nankai University Catalyst) was used to replace the graphene aerogel A1 to obtain a regenerated catalyst DS2.

[0215] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst DS2 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst DS2 were determined by pyridine infrared method. The test results are shown in Table 2.

[0216] Comparative Example 3

[0217] The method in Example 1 was followed, except that an equal amount of graphene aerogel DA1 was used to replace A1, to obtain a regenerated catalyst DS3.

[0218] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst DS3 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst DS3 were determined by pyridine infrared method. The test results are shown in Table 2.

[0219] Comparative Example 4

[0220] The GO slurry obtained in Preparation Example 1, ethylenediamine and commercially available aluminum oxide were mixed, with a mass ratio of ethylenediamine to graphene oxide of 0.004:1, and then ultrasonically stirred and reacted in a drying oven at 95°C for 12 hours. Then, the mixture was frozen in a box at -18°C. After being completely frozen, the sample was placed in a vacuum freeze dryer for freeze drying, and the obtained solid product was recorded as DS4.

[0221] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst DS4 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst DS4 were determined by pyridine infrared method. The test results are shown in Table 2.

[0222] Comparative Example 5

[0223] The method in Example 1 was followed, except that an equal amount of graphene aerogel DA2 was used to replace A1, to obtain a regenerated catalyst DS5.

[0224] By N 2 The specific surface area, total pore volume and pore size distribution of the regenerated catalyst DS5 were tested by adsorption-desorption isotherms. The B acid and L acid contents of the regenerated catalyst DS5 were determined by pyridine infrared method. The test results are shown in Table 2.

[0225] The physical and chemical data of the regenerated catalysts prepared in the above examples and comparative examples are listed in Table 2.

[0226] Table 2

[0227]

[0228]

[0229] The regenerated catalysts prepared in the above examples and comparative examples were evaluated for regeneration using an alcohol amine solution.

[0230] CO2-rich 2 Preparation of amine solution: 2 / CO 2 The gas was passed into the complex amine solution at a volume ratio of 85:15 for 2 h to obtain a CO-rich2 Amine solution.

[0231] 1% (in the rich CO 2 The above regenerated catalyst (mass ratio of amine solution) is added to the rich CO 2 The temperature of the amine solution was gradually raised and stirred continuously at a stirring speed of 200 rpm. A gas flow meter was used to control and record the desorbed CO 2 The cumulative volume flow rate was recorded, and the temperature at the start of desorption (initial temperature), the end temperature, and the regeneration time were recorded. The rich solution was sampled every 5 minutes, and the CO in the composite amine solution at different desorption times was tested by acid-base titration. 2 The loading amount was used to calculate the desorption rate, desorption amount and relative energy consumption. The results are shown in Table 3.

[0232] Desorption energy consumption (H) refers to the unit mole of CO 2 The desorption energy consumption (kJ / mol) is defined as the energy input rate and CO 2 The ratio of desorption rate is calculated by formula (1):

[0233]

[0234] Among them, E refers to the CO recorded by the electric energy meter within a certain period of time. 2 The power consumed by desorption is in kW·h and needs to be converted into kJ when used.

[0235] The relative energy consumption (RH) was calculated by formula (2), where Hb (kJ / mol) is the desorption energy consumption of the blank control solution during the regeneration process, and Hi (kJ / mol) is the catalytic CO 2 The desorption energy consumption of the desorption process,

[0236]

[0237] The amine solution regeneration experiment was repeated 6 times for each regenerated catalyst, and then the regenerated catalyst after the reaction was dried and weighed, and the catalyst mass loss rate was calculated.

[0238] Loss rate (%) = (mass of freshly regenerated catalyst - mass of regenerated catalyst after 6 regenerations) / mass of freshly regenerated catalyst × 100%.

[0239] Table 3

[0240]

[0241]

[0242] Combining the results in Tables 1-3, it can be seen that when the graphene aerogel provided by the present invention is used as a catalyst carrier to prepare a regenerated catalyst for regenerating an alcohol amine solution, the CO 2 The desorption effect can be improved, the initial desorption temperature can be lowered, and thus the energy consumption of the desorption process can be reduced.

[0243] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A graphene aerogel, characterized in that: The graphene aerogel has a B acid content of 0.001-0.05 mmol / g and a specific surface area of ​​40-200 m 2 / g, the volume of pores with a pore diameter below 20nm accounts for no less than 50% of the total pore volume of the graphene aerogel.

2. The graphene aerogel according to claim 1, wherein: The B acid content of the graphene aerogel is 0.01-0.03 mmol / g; Preferably, the specific surface area of ​​the graphene aerogel is 100-120m 2 / g.

3. The graphene aerogel according to claim 1 or 2, wherein: The total pore volume of the graphene aerogel is 0.01-0.5 mL / g, preferably 0.1-0.3 mL / g; Preferably, in the graphene aerogel, the volume of pores with a pore diameter of less than 20 nm accounts for 55-90% of the total pore volume of the graphene aerogel, and more preferably 70-80%.

4. The graphene aerogel according to any one of claims 1 to 3, wherein: The graphene aerogel contains C element, O element and N element, and the molar ratio of the C element, O element and N element is (1-60): (5-30): (0.5-5); preferably (15-35): (10-20): (1-2); Preferably, the oxygen species in the graphene aerogel measured by X-ray photoelectron spectroscopy include hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen, and the molar ratio of hydroxyl oxygen, carbonyl oxygen and carboxyl oxygen is (1-20): (0.1-5): (1-5), preferably (1-5): (0.5-2): (1-2).

5. The graphene aerogel according to any one of claims 1 to 4, wherein: The graphene aerogel has a three-dimensional porous network structure formed by stacking two-dimensional graphene sheets; Preferably, the average sheet thickness of the two-dimensional graphene sheet is 10-200 nm, preferably 50-100 nm; Preferably, the average sheet length of the two-dimensional graphene flakes is 0.1-10 μm, preferably 1-5 μm.

6. The graphene aerogel according to any one of claims 1 to 5, wherein: The compressive strength of the graphene aerogel is higher than 30 kPa, preferably 40-50 kPa.

7. A regenerated catalyst, characterized in that: The regenerated catalyst comprises a carrier and a metal component supported on the carrier; the metal component has Lewis acid properties, and the carrier is the graphene aerogel according to any one of claims 1 to 6.

8. The regenerated catalyst according to claim 7, wherein The B acid content in the regenerated catalyst is 0.0005-0.02 mmol / g, more preferably 0.008-0.016 mmol / g; Preferably, in the regenerated catalyst, the molar ratio of B acid to L acid is 0.01-1:1, preferably 0.1-0.5:1, and more preferably 0.1-0.2:

1.

9. The regenerated catalyst according to claim 7 or 8, wherein Based on the total mass of the regenerated catalyst, the content of the carrier is 30-70wt%, preferably 30-50wt%; calculated as oxide, the content of the metal component is 30-70wt%, preferably 50-70wt%.

10. The regenerated catalyst according to any one of claims 7 to 9, wherein: The metal component is selected from transition metal elements and / or Group IIIA elements, preferably at least one of Fe, Mn, Co, Ni, Cu, Zn, La, Ce, Zr, Mo, W, Au, Ag, Ti, Pt, Rh, Ru, Re, Al, Ga and In, and more preferably at least one of Al, Fe, Co, Ni and Ti.

11. The regenerated catalyst according to any one of claims 7 to 10, wherein: The specific surface area of ​​the regenerated catalyst is 30-100m 2 / g, preferably 45-80m 2 / g; Preferably, the total pore volume of the regenerated catalyst is 0.06-0.2 mL / g, preferably 0.1-0.15 mL / g; Preferably, in the regenerated catalyst, the volume of pores with a pore diameter of less than 20 nm accounts for no less than 30% of the total pore volume of the regenerated catalyst, preferably 30-80%, and more preferably 50-60%.

12. Use of the regeneration catalyst according to any one of claims 7 to 11 in the regeneration of a CO2-rich amine solution.

13. A method for regenerating a CO2-rich amine solution, characterized in that: Under regeneration conditions, the CO2-rich amine solution is contacted with the catalyst to desorb CO2; Wherein, the catalyst is the regenerated catalyst according to any one of claims 7 to 11; Preferably, the amount of the catalyst is 1-10wt%, preferably 1-3wt%, based on the total mass of the CO2-rich amine solution; Preferably, the initial temperature of the CO2 desorption is 10-70°C, preferably 30-50°C.

Citation Information

Patent Citations

  • Expanded perlite with catalytic cross-link effect and preparation method of expanded perlite

    CN103058540A

  • Graphene aerogel and preparation method and application thereof

    CN107585758A

  • Graphene aerogel or carbon nano-particle phase change material and preparation method thereof

    CN110564374A

  • Preparation method of MgAl-LDH-loaded amino-functionalized graphene aerogel

    CN115634628A

  • Convergence sea farm application of NANO bubble

    KR102248961B1

Cited By

  • Graphene aerogel, regenerated catalyst and use thereof, and method for regenerating co2-rich amine solution

    EP4748789A1